Plated versus Corrugated Web Steel Girders in Shear: Behavior, Parametric Analysis, and Reliability-Based Design Optimization - Moussa Leblouba; Abdul Saboor Karzad; Sami W. Tabsh; Samer Barakat (Buildings, 2022)
Unlike straight web I-girders, the construction industry’s demand for corrugated web steel girders is increasing due to their high shear strength without needing transverse stiffeners. Although the corrugation fabrication cost could be high, savings on material, transportation, and erection costs can compensate for the expenditures needed to build flat-plated girders with stiffeners. This study investigates the shear behavior of straight and corrugated webs with different geometries and corrugation profiles (triangular and trapezoidal) through laboratory testing. Following a detailed parametric study, the results of the experimental program were used to formulate a reliability-based design optimization (RBDO) problem to achieve target reliability. When applied to two case studies related to girders of a building and a bridge, the RBDO demonstrated that it is possible to design girders with corrugated webs to achieve economic designs in terms of material volume in the range of 20% to 40% with thinner webs and without the need for transverse stiffeners.